The contribution of placement school experiences to prospective teachers’ multicultural competence development: Ethiopian secondary schools in focus - Solomon Melesse; Dawit Mekonnen (Intelektual Pustaka Media Utama, 2020)
This study was designed to examine the contribution of placement school experiences to prospective teachers’ multicultural competence development in Ethiopia. The major sources of data were prospective teachers of the three randomly selected Teacher Education Institutes who took their placement school experiences at the respective secondary schools. Two hundred and forty prospective teachers were selected from five hundred and seventy three prospective teachers of the 2011/2012 academic year cohort using a proportional random sampling technique to fill in the questionnaire. Fifteen prospective teachers were also selected for interview using purposive sampling technique. Data were collected through questionnaire and interview. The data collected through the questionnaire were analyzed using percentage and one sample t-test. Interview data were reported in words following themes made vis-à-vis the research questions of this study. The findings of the study pointed out that collaboration among prospective teachers, staffs of placement schools, and students’ parents have brought the required multicultural knowledge, attitude, and skill to prospective teachers. However, the findings noted that learner-centered knowledge construction philosophy is at its infant stage at the placement schools. In light of these findings, relevant recommendations have been made in the paper.